2021
DOI: 10.3390/ijerph182413096
|View full text |Cite
|
Sign up to set email alerts
|

Parks and the Pandemic: A Scoping Review of Research on Green Infrastructure Use and Health Outcomes during COVID-19

Abstract: Green infrastructure (GI) has long been known to impact human health, and many academics have used past research to argue for the potential importance of GI as a mechanism for maintaining or improving health within the context of the COVID-19 pandemic. This scoping review addresses the question: What evidence, if any, have researchers found of a relationship between green infrastructure use and health during the COVID-19 pandemic? Specifically, evaluating the (a) association of GI use with COVID-19 disease out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 63 publications
0
21
0
2
Order By: Relevance
“…All of these considerations, already important worldwide per-pandemic, have become increasingly urgent and significant post-pandemic. There is now very extensive research detailing the effects of COVID-19 itself, and associated personal and social disruptions, on: deterioration in mental health [ 51 , 74 , 75 , 94 , 95 , 96 , 97 , 98 ]; access to, and enjoyment of nature during the pandemic [ 99 , 100 , 101 , 102 ]; and the effects of nature on maintaining mental health [ 103 , 104 , 105 , 106 , 107 ]. There is also a growing body of statistical and modelling information on the effects of the pandemic in decreasing economic productivity at various scales [ 108 , 109 , 110 , 111 , 112 ].…”
Section: Conclusion: Progress and Prospects Post-pandemicmentioning
confidence: 99%
“…All of these considerations, already important worldwide per-pandemic, have become increasingly urgent and significant post-pandemic. There is now very extensive research detailing the effects of COVID-19 itself, and associated personal and social disruptions, on: deterioration in mental health [ 51 , 74 , 75 , 94 , 95 , 96 , 97 , 98 ]; access to, and enjoyment of nature during the pandemic [ 99 , 100 , 101 , 102 ]; and the effects of nature on maintaining mental health [ 103 , 104 , 105 , 106 , 107 ]. There is also a growing body of statistical and modelling information on the effects of the pandemic in decreasing economic productivity at various scales [ 108 , 109 , 110 , 111 , 112 ].…”
Section: Conclusion: Progress and Prospects Post-pandemicmentioning
confidence: 99%
“…Apart from that, economic benefits in terms of higher land and property value, increased investment and spending, as well as environmental cost-saving are also the direct outcomes of spaces and cities with more GI elements (Choi et al, 2021;Hansen et al, 2019;Kim, 2016;Gore et al, 2013). Moreover, improved physical and mental health benefits following the recent global Covid-19 pandemic are linked with urban areas that have more GI elements (Pamukcu-Albers et al 2021;Heckert & Bristowe 2021;Hanzl, 2021). In particular, scholars have highlighted the importance and advantage of a tactical approach in transforming urban spaces to create more green areas that benefit the general public.…”
Section: Benefits Of the Gi Approach For Residual Space Underneath El...mentioning
confidence: 99%
“…We described their potential limitations below: Research has indicated that there are potential positive and negative correlations between frequency of park visits and health outcomes during the COVID-19 pandemic. Thus, it is uncertain whether frequent visits to parks are the risky behavior of COVID-19 or beneficial for health ( Heckert and Bristowe, 2021 ). Public transit infrastructure and access vary greatly by county, and some counties do not have sufficient budgets or/and demand to establish public transit, which may mislead the mobility measure ( Nichols and Taylor, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that there are potential positive and negative correlations between frequency of park visits and health outcomes during the COVID-19 pandemic. Thus, it is uncertain whether frequent visits to parks are the risky behavior of COVID-19 or beneficial for health ( Heckert and Bristowe, 2021 ).…”
Section: Introductionmentioning
confidence: 99%